BERDAMAI DENGAN PERBEDAAN: PERAN PENDIDIKAN MULTIKULTURAL TERHADAP PERSEPSI SISWA MUSLIM TERHADAP TEMAN SEBAYA NONMUSLIM DI SEKOLAH MENENGAH ATAS - Adnan Fajar Rivai; Natsir, Ahmad; Muzakki, Hawwin; Ahmad Yuzki Faridian Nawafi; Ahmad Fahrudin (MA'ALIM: Jurnal Pendidikan Islam, 2025)
This study examines Muslim students' perceptions of religious moderation towards non-Muslim peers and the role of multicultural education in fostering tolerance at SMAN 1 Karas, against the backdrop of interreligious conflicts among school-aged adolescents. Employing a qualitative approach, data were collected through observations, in-depth interviews, and documentary analysis, with triangulation applied to ensure validity. The findings reveal three key insights: firstly, Islamic Religious Education (PAI) and Character Education teachers play a pivotal role in instilling multicultural values through classroom instruction, mentoring, and collaborative extracurricular activities, emphasising principles of justice, equality, and respect for diversity rooted in Islamic teachings. Secondly, Muslim students predominantly exhibit positive attitudes towards non-Muslim peers, perceiving religious pluralism as integral to Islamic values that uphold fairness and mutual recognition. Thirdly, harmonious interfaith interactions are evident in both academic settings—such as group discussions and collaborative projects—and non-academic spheres, including basketball, scouting, and English club activities, which serve as practical platforms for embodying pluralism and democratic values. The study concludes that SMAN 1 Karas’s integrative approach to multicultural education effectively promotes religious moderation and mitigates sectarian tensions, recommending its contextual adaptation for other educational institutions. These findings contribute to broader discourses on inclusive pedagogy and institutional strategies for nurturing tolerance, underscoring the interplay between curricular frameworks, teacher agency, and student-led socialisation processes in shaping interreligious dynamics within school environments.